1990
DOI: 10.1056/nejm199005243222104
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Serum Lipoprotein(a) Concentration and Apolipoprotein(a) Phenotype to Coronary Heart Disease in Patients with Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia carries a marked increase in the risk of coronary heart disease (CHD), but there is considerable variation between individuals in susceptibility to CHD. To investigate the possible role of lipoprotein(a) as a risk factor for CHD, we studied the association between serum lipoprotein(a) levels, genetic types of apolipoprotein(a) (which influence lipoprotein(a) levels), and CHD in 115 patients with heterozygous familial hypercholesterolemia. The median lipoprotein(a) level in the 54 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
180
3
8

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(205 citation statements)
references
References 34 publications
14
180
3
8
Order By: Relevance
“…Thus, an earlier study showed an increased prevalence of those genetic isoforms of apo(a) that are associated with high serum Lp(a) concentrations in FH patients with CHD compared with those without CHD. 17 In our own study family membership continued to operate as an independent influence on serum Lp(a) concentration, as it does in the general population. 23 However, it is clearly not the case that genetic effects unrelated to the FH gene defect can be the major explanation for the increase in Lp(a) in patients with FH because the presence of the gene still doubles the mean Lp(a) level even when family membership was controlled for, as in the present investigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, an earlier study showed an increased prevalence of those genetic isoforms of apo(a) that are associated with high serum Lp(a) concentrations in FH patients with CHD compared with those without CHD. 17 In our own study family membership continued to operate as an independent influence on serum Lp(a) concentration, as it does in the general population. 23 However, it is clearly not the case that genetic effects unrelated to the FH gene defect can be the major explanation for the increase in Lp(a) in patients with FH because the presence of the gene still doubles the mean Lp(a) level even when family membership was controlled for, as in the present investigation.…”
Section: Discussionmentioning
confidence: 98%
“…We did not demonstrate any association between Lp(a) level and clinically overt CHD in our patients with FH. Both Seed and her coworkers 17 and Wiklund and colleagues 16 have recently reported that Lp(a) concentrations are higher in FH heterozygotes who have developed CHD than in those who have not. In both studies the criteria for identifying patients with CHD were similar to those in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Step OR 95% CL independent correlate for the presence of coronary heart disease among whites and Japanese Americans Seed et al 1990), and it has also been identified as an independent risk factor for myocardial infarction (Rhoads et al 1986), as well as for atherogenesis and thromboembolytic events (Scott 1989). Levels of Lp(a) in serum are genetically determined, and these levels do not correlate in general with other plasma lipids (Utermann 1989).…”
Section: Discussionmentioning
confidence: 99%
“…A variation of apoA-I (delta K107) was associated with this syndrome. Increases of lipoprotein(a) (Lp(a)) 75 , of fibrinogen 76 and plasma homocysteine [77][78][79][80][81] may contribute to some cases of CAD. The relationship of homocysteine and atherosclerosis was first reported in 1969, when McCully 82 demonstrated precocious atherosclerosis in children with homocystinuria.…”
Section: Risk Factorsmentioning
confidence: 99%